Longitudinal Course of Short-Term Variation and Doppler Parameters in Early Onset Growth Restricted Fetuses - Baier, Friederike; Weinhold, Leonie; Stumpfe, Florian M.; Kehl, Sven; Pretscher, Jutta; Bayer, Christian M.; Topal, Nalan; Pontones, Constanza; Mayr, Andreas; Schild, Ralf; Schmid, Matthias; Beckmann, Matthias W.; Faschingbauer, Florian (Ultraschall in der Medizin - European Journal of Ultrasound, 2020)
Purpose To evaluate the longitudinal pattern of fetal heart rate short term variation (STV) and Doppler indices and their correlation to each other in severe growth restricted (IUGR) fetuses.Materials and Methods In this retrospective study, pregnancies with a birth weight below the 10th percentile, born between 24 and 34 gestational weeks with serial Doppler measurements in combination with a computerized CTG (cCTG) with calculated STV were included. Longitudinal changes of both Doppler indices and STV values were evaluated with generalized additive models, adjusted for gestational age and the individual. For all measurements the frequency of abnormal values with regard to the time interval before delivery and Pearson correlations between Doppler indices and STV values were calculated.Results 41 fetuses with a total of 1413 observations were included. Over the course of the whole study period, regression analyses showed no significant change of STV values (p = 0.38). Only on the day of delivery, a prominent decrease was observed (mean STV d28-22: 7.97 vs. mean STV on day 0: 6.8). Doppler indices of UA and MCA showed a continuous, significant deterioration starting about three weeks prior to delivery (p = 0.007; UA and p < 0.001, MCA). Correlation between any Doppler index and STV values was poor.Conclusion Fetal heart rate STV does not deteriorate continuously. Therefore, cCTG monitoring should be performed at least daily in these high-risk fetuses. Doppler indices of umbilical artery (UA) and middle cerebral artery (MCA), however, showed continuous deterioration starting about 3 weeks prior to delivery.
Keywords: doppler; fetal distress; short-term variation; computerized CTG